Capacity-based seismic design of a middle-rise residential building in an area of moderately-high seismicity. Issue 1 (December 2020) - Hidayat, Banu Ardi; Haryanto, Yanuar; Nuroji; Sukamta; Praja, Wisnu Kurnia; Hu, Hsuan-Teh
Abstract: As Indonesia is located across three active tectonic plates, it is prone to a high potential earthquake threat. Strict regulations have been introduced to prevent damage to buildings caused by seismic activity. This study aims to examine the behavior of a middle-rise residential building in a moderately-high seismicity area (i.e. Semarang City) and the design of the Reinforced Concrete (RC) members under seismic load. The design was based on the capacity method and the strong column-weak beam concept was applied to the plastic hinge effect that occurred in the beam. Therefore, the analytical computation was performed, taking the structural seismic response into account. Also, the code-based design calculation of RC members was achieved. The measured structural response showed that the building fulfilled the requirements stated in the Indonesia Code of Earthquake-based Design. The first two modes of the building translated in the Y and X directions, which is the preferred response under the earthquake. The story-drifts that occurred were within the acceptable limits and the structural stiffness in the X and Y directions were found to be similar. Finally, the exact design of RC members was found to satisfy the code.